The successful management of a Bronchoesophageal fistula after lung transplantation: a case report. (31st March 2015) - Camagni, Stefania; Lucianetti, Alessandro; Ravelli, Paolo; Di Dedda, Giovanni B.; Bonanomi, Ezio; Corno, Vittorio; Aluffi, Alessandro; Pinelli, Domenico; Zambelli, Marco F.; Guizzetti, Michela; Parigi, Piercarlo; Colledan, Michele
Summary We describe an unprecedented, disastrous complication after bilateral lung transplantation (BLT), a bilateral bronchial dehiscence with a right bronchoesophageal fistula leading to life‐threatening septic shock. We also report the successful endoscopic management of this complication by double stenting and stress the efficacy of the multidisciplinary approach to this critical case.